Strategy to Increase Market Reach of Roti Nova MSMEs, Gunung Anyar District, Surabaya Through GoBiz Registration: Strategi Peningkatan Jangkauan Pasar UMKM Roti Nova Kelurahan Gunung Anyar Surabaya Melalui Pendaftaran GoBiz - Alvina Marcelia; Ira Wikartika (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
PKKM Bina Desa is a community service activity carried out by student groups with the aim of solving problems in an area to achieve equitable development. One of the student groups at the East Java "Veteran" National Development University carried out PKKM Village Development activities to assist the "Roti Nova" MSMEs located in the Gunung Anyar sub-district area, Surabaya City. Digital marketing is still minimally delivered and implemented by MSMEs in Gunung Anyar Village. The promotion and sales sector are one of the sectors that relies on digital information technology, including sales via the GoBiz platform. So far, Roti Nova UMKM has carried out marketing using conventional methods and participated in several activities such as offline bazaars and events organized by Gunung Anyar Village, so its marketing is still not extensive. With increasingly rapid technological developments, conventional marketing is considered less than optimal. Registration with GoBiz is intended to facilitate MSME players in digital marketing, as a step to develop their business by achieving better product marketing results. The method of implementing the activities used was by conducting interviews, observing, and assisting the owners of Roti Nova MSMEs. The results of this activity include increasing knowledge about digital marketing and expanding market reach which has an impact on increasing the income of Roti Nova MSMEs. With this activity, it is hoped that Gunung Anyar Village can provide further learning related to digital marketing to its community, especially to MSMEs.